Pendampingan Penyusunan E-Modul Kolaboratif bagi Guru SMK Pusat Keunggulan (SMK PK) - Tri Candra Wulandari; Zainal Abidin (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service activity is to assist SMK PK teachers to produce collaborative e-modules. The collaboration that is expected to be realized is the existence of an e-module collaboration on productive materials with mathematics, collaborative e-modules between productive materials. The main obstacle to the implementation of SMK PK lies in the teachers, because not all teachers are able to adapt quickly to change. This service activity is carried out through three stages, namely preparation, implementation and evaluation and follow-up. At the implementation stage, this community service activity uses 2 activities, namely workshops and mentoring. The result of the assistance is the creation of a collaboration module between informatics subjects in computer and network engineering expertise programs, mathematics with catering services and in nursing subjects